PENGARUH MINAT BELAJAR TERHADAP PRESTASI BELAJAR FISIKA PADA SISWA DI SMAN 11 KOTA JAMBI - Rivani, Putri Ayu; Kurniawan, Dwi Agus; Yohafrinal, Yohafrinal (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
The teaching and learning process is indeed very influential on students' interest in learning in the success of students in receiving and understanding the material presented. In the competence of learning physics in order to achieve the objectives of learning if students have an increase in learning achievement, especially in the field of physics. This study uses a type of quantitative method. The data sources used are in the form of question questionnaires and interest questionnaires. The total subjects are 56 students. From class X MIPA 1 there are 31 students and X MIPA 2 are 25 students. From the test results, it was found that students' interest in learning physics was quite good because not many students had difficulties in understanding the material from the physics lesson. Even so, students at SMA Negeri 11 Jambi City have achievements that are not too low and are still classified as moderate. From the regression test conducted, it was found that students' interest in learning had an influence on student achievement. With this influence, students who have an interest in general will easily understand physical lessons.